WSV399, a viral tegument protein, interacts with the shrimp protein PmVRP15 to facilitate viral trafficking and assembly. (June 2016) - Jaree, Phattarunda; Senapin, Saengchan; Hirono, Ikuo; Lo, Chu-Fang; Tassanakajon, Anchalee; Somboonwiwat, Kunlaya
Abstract: Viral responsive protein 15 ( Pm VRP15) has been identified as a highly up-regulated gene in the hemocyte of white spot syndrome virus (WSSV)-infected shrimp Penaeus monodon . However, the function of Pm VRP15 in host–viral interaction was still unclear. To elucidate Pm VRP15 function, the interacting partner of Pm VRP15 from WSSV was screened by yeast two-hybrid assay and then confirmed by co-immunoprecipitation (Co-IP). Only WSV399 protein was identified as a Pm VRP15 binding protein; however, the function of WSV399 has not been characterized. Localization of WSV399 on the WSSV virion was revealed by immunoblotting analysis ( in vitro ) and immunoelectron microscopy ( in vivo ). The results showed that WSV399 is a structural protein of the WSSV virion and is particularly located on the tegument. Gene silencing of wsv399 in WSSV-infected shrimp reduced the percentage of cumulative mortality by 74%, although the expression level of a viral replication marker gene, vp28, was not changed suggesting that WSV399 might not involved in viral replication but viral assembly. Because it has already been known that tegument proteins function in capsid transport during viral trafficking and assembly, interaction between Pm VRP15 on hemocyte nuclear membrane and the WSV399 viral tegument protein suggests that Pm VRP15 might be required for trafficking and assembly of WSSV during infection. Highlights: Pm VRP15, a WSSV-responsive gene, can interact with a viral protein, WSV399. WSV399 is a structural protein of the WSSV virion particularly located on the tegument. Interaction between Pm VRP15 and WSV399 might be required for trafficking and assembly of WSSV during infection.